Capital investment & financing a practical guide to financial evaluation - Agar, Christopher (Amsterdam ; London : Elsevier, 2005)
The requirement to maximise value for shareholders is at the core of any corporate investment or financing decision. The intrinsic value of proposed investments should be assessed before deciding how much capital to allocate; the benefits and risks associated with each available source of finance should be considered when capital is being raised; and capital, and any associated financial risks, should be managed in a way that continues to maximise value. At every stage, an analysis should be carried out to ensure the decision is optimal for shareholders and other capital providers. This book provides practical guidance on the application of financial evaluation techniques and methods (mainly covered in Appendices), as well as comprehensive coverage of traditional corporate finance topics, discussed in the context of capital investment, raising and management and financial risk management (using derivatives). Models, formulae and other quantitative techniques are illustrated in over 100 examples (using only basic mathematics). Topics discussed include the following: * business appraisal using financial ratios * corporate valuation (mainly discounted cash flow and real options) *investment appraisal techniques * acquisition structuring and evaluation * the nature of loans and loan agreements * features and pricing of bonds (straight and convertible) * leasing (including leveraged leasing) * equity raising (Initial Public Offerings) * long and short term capital management * basic pricing of derivatives (forwards, futures, options, swaps) * interest rate and currency risk management using derivatives Capital Investment & Financing provides a comprehensive, in-depth coverage of concepts, methods and techniques involved when evaluating acquisitions and other investments, assessing financing opportunities, and managing capital. The core chapters provide practical guidance on key corporate finance topics; the Appendices contain more quantitative material, focusing on pricing techniques. Examples are used throughout, and an integrated case study (fictional) in the final Appendix uses many of the techniques discussed. *Discusses all key areas of corporate investing and financing, focusing on key financial issues *Concise, thorough and technical, it enables to reader to acquire knowledge effectively *Can be used in everyday analysis and decision making.
List of Equations. Examples, and Exhibits. Preface. Chapter 1 - CAPITAL INVESTMENT: Introduction. Capital Expenditure on Tangible Assets. Acquisitions an Overview. Corporate Valuation. Acquisition Structuring and Evaluation. Chapter 2 - CAPITAL RAISING: Introduction. Debt. Equity. Chapter 3 - CAPITAL MANAGEMENT: Introduction. Long Term Capital Management. Short Term Capital Management. Chapter 4 - FINANCIAL RISK MANAGEMENT: Introduction. Interest Rate Risk. Currency Risk. Appendix A Financial Ratios. Appendix B Pricing Techniques. Appendix C Leasing. Appendix D Examples. Bibliography. Index.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Capital investments; Corporations -- Finance; Entreprises -- Finances; Electronic books